Studying novel sporulation genes in Clostridium sporogenes - Rizvi, Syeda-Rubab-Zehra (2020)
The class Clostridia consists of bacteria that are ubiquitous in nature, but are of high significance in various aspects of life, namely health, disease, food spoilage, biofuel production, bioterrorism and cancer therapy. Most of the clostridial species produce resilient spores, which ensure their survival under harsh environments up to several years in the form of dormant refractile bodies; and once they find favourable growth conditions, they germinate into their metabolically active forms. As much as this phenomenon is astounding, the current knowledge about clostridial sporulation mechanisms is also very limited. This situation calls for exploiting the forward genetics approach, by using transposable elements to identify novel sporulation genes in a relatively-accessible, non-pathogenic strain of Clostridium sporogenes. In conditional transposon mutagenesis, a mariner-based transposon is allowed to jump into random genes on host chromosome by means of Himar1 transposase enzymes, which eventually generates a library of transposon mutants that can be screened for the desired phenotype and ultimately, the genotype. Hence, transposon-insertion mutant libraries were constructed in C. sporogenes, from which 5,061 mutants were randomly screened for sporulation or germination defects, on the basis of little or complete loss of heat-resistant spores. Out of the 41 isolated sporulation- or germination-defective mutants, 28 unique genes were identified to have potential roles in sporulation or germination. According to annotations from the NCBI genome database, the identified genes encode for proteins involved in various stages of sporulation, cell division, DNA translocation, and some other biological processes. This indicates that the defects in sporulation or germination in the corresponding C. sporogenes mutants were either caused through the direct or indirect disruption of their cascades. Among the identified sporulation or germination genes, CLSPO_RS15205 (yqfD), CLSPO_RS07560 (divIVA), CLSPO_RS16880 (clpX), CLSPO_RS17345 (spoVK) and CLSPO_RS00950 (spoIID) were selected for CRISPR/Cas9-based targeted genome editing and the resulting null mutants were further characterized. In brief, attempts were made to determine possible roles of the target genes in the survival, growth, haemolysis, proteolysis and cell and colony morphology of C. sporogenes mutant strains. This characterization of general biology and sporulation profile of the acquired mutants will not only aid in better understanding sporulation mechanisms in C. sporogenes, but also for its toxigenic surrogate Group A proteolytic Clostridium botulinum. The acquired data is aimed to help spores-based applications in cancer therapy and food safety research.